Size and competitiveness : an examination of the CARICOM Single Market and Economy (CSME) - Mohammed, Debbie A. (2008)
Advances the view that the survival of CARICOM states necessitates fundamental economic restructuring aimed at developing new, globally competitive industries, and strategic regional and global repositioning to operationalize and sustain this new development path. Argues that smallness poses particularly severe challenges for individual economies to overcome. Advocates a regional approach to development with the CSME as the principle driver. Notes also that CSME's ability to meet regional competitiveness and development expectations must also be critically examined.